Nepal, nostalgia and modernity - Shimkhada, Deepak (Mārg publications, 2011)
Contributed articles on Nepali art, architecture, performances, and religious traditions
Contributed articles. - Distributor statement from jacket. - Includes bibliographical references and index
Keywords: Nepal -- Religious life and customs; Kunst; Architektur; Nepal